The application of the make-a-match cooperative learning model to improve civics learning outcomes - Nurjanah, Nurjanah; Samsuri, Samsuri; Ramadan, Syahri (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
The study aims to reveal the learning outcome in the civic education of Junior High School  2 Wates students by implementing the cooperative learning model "Make A Match" type with film media on competency standard understanding of various constitutions used in Indonesia. This research is classroom action research conducted in three cycles. The technique used for data collection was observation and achievement test. The data analysis technique used the procedure of data reduction, data presentation, and conclusion drawing. The results show increased student learning outcomes in the cognitive, affective, and psychomotor domains from the first to the second and third cycles. It can be concluded from this study that implementing the cooperative learning model of "Make A Match" type with film media can improve the learning outcomes in the civic education of the students of class VIII C Junior High School  2 Wates in the academic year of 2015/2016. Therefore it can be used as an alternative learning model in civic education.